Identification of hardness values of boiler pipes after heating and without heating process - Mulia, Mulia; Suardi, Suardi; Susilo, Hendra; Sinurat, Fadlah K.; Supriadi, Supriadi (Trigin Publisher, 2024)
Boilers operate at high pressure and high temperature. When the life of the boiler pipe reaches its limit, failure will occur. High temperatures on the outside of the pipe, high pressure inside, and also flames that have been contaminated with corrosive residues for a long amount of time will cause pipe failure. The purpose of the study was to identify the hardness value of boiler pipes after experiencing the heating process and without heating on ASTM A179 pipes. The research method carried out is starting from the preparation of tools and materials, cutting small materials (making specimens), hardness testing, data processing, data analysis and drawing conclusions. The research results are as follows: 1) Obtained average hardness values on standard ASTM A179 pipes in boilers with each brinell, Rockwell, and Vickerss test of 63.67 HRB, 45.20 HRC, and 85.20 HV. 2). The average hardness value of ASTM A179 pipes affected by boiler combustion chamber temperature with each brinell, Rockwell, and Vickerss test is 76 HRB, 50.40 HRC, and 202.30 HV. 3) The value of hardness test results on standard ASTM A179 pipes comparing with after heating has increased hardness in each brinell test by 63.67: 76 HRB, Rockwell by 24.20: 50.40 HRC, and Vickerss of 85.20: 202.30 HV.